2013
DOI: 10.1159/000351473
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 Expression Is Related to High Ki-67 Index and Poor Prognosis in Lymph Node-Positive Breast Cancer Patients

Abstract: Background: Recent preclinical studies have shown that Forkhead box protein 3 (FOXP3) is an important tumor suppressor gene. The clinical and prognostic implication of FOXP3 expression in breast cancer cells still remains controversial. Methods: We evaluated the FOXP3 expression status of 183 patients who underwent curative surgery for breast cancer using the immunohistochemical assay of tissue microarray. Results: We found FOXP3 expression in 51 out of 183 (27.9%) surgically resected breast cancer tumors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
2
11
2
Order By: Relevance
“…These authors attributed the correlation with worse prognosis to Treg infiltration. Other study using immunohistochemistry technique also showed association of FOXP3 expression by tumor cells with higher histological grade [48]. However, in this study, all tumor samples showed cytoplasmic or both cytoplasmic and nuclear FOXP3 expression, suggesting frequent deregulation of FOXP3 localization and failure to translocate to the nucleus in breast cancer cells and explaining the correlation with worse prognosis.…”
Section: Discussioncontrasting
confidence: 54%
“…These authors attributed the correlation with worse prognosis to Treg infiltration. Other study using immunohistochemistry technique also showed association of FOXP3 expression by tumor cells with higher histological grade [48]. However, in this study, all tumor samples showed cytoplasmic or both cytoplasmic and nuclear FOXP3 expression, suggesting frequent deregulation of FOXP3 localization and failure to translocate to the nucleus in breast cancer cells and explaining the correlation with worse prognosis.…”
Section: Discussioncontrasting
confidence: 54%
“…FOXP3 was also a strong prognostic factor for distant metastasis-free survival, but not for local recurrence incidence risk (Merlo et al, 2009). These results were confirmed by other 2 independent studies (Kim MH et al, 2013;Nair et al, 2013). The frequency of FOXP3 positive cancer cells in primary gastric tumors correlated with the incidence of lymph node metastases (Yoshii et al, 2012;Wang et al, 2010) and the 3-year survival rate, indicating a potential association of FOXP3 expression with poor prognosis.…”
Section: Foxp3 Expression and Prognosis In Human Cancersupporting
confidence: 70%
“…As it has been described that several tumor entities are positive for Foxp3, CTLA-4 or CD39/CD73 [6, 1618], all of them Treg associated markers, we reasoned whether also GARP, a recently described Treg activation marker involved in tolerance induction[9], is expressed on melanoma cells and would functionally contribute to the inhibitory features mentioned above. We found a significant expression of GARP and Foxp3 on melanoma cell lines SK29-MEL-1 (Figure 2A) and UKRV-Mel-15a, UKRV-Mel-21a, Ma-Mel-59a and Ma-Mel-91a (Suppl.…”
Section: Resultsmentioning
confidence: 99%